2007
DOI: 10.1254/jphs.fp0061235
|View full text |Cite
|
Sign up to set email alerts
|

Pravastatin Inhibits Arrhythmias Induced by Coronary Artery Ischemia in Anesthetized Rats

Abstract: Abstract. We have reported that chronically administered pravastatin prevented coronary artery reperfusion-induced lethal ventricular fibrillation (VF) in anesthetized rats without lowering the serum cholesterol level. The present study was undertaken to evaluate whether pravastatin prevents ischemia-induced lethal VF, simultaneously examining myeloperoxidase (MPO) activity in ischemic myocardial tissues. Anesthetized rats were subjected to 30-min ischemia and 60-min reperfusion after chronic administration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 38 publications
2
14
0
Order By: Relevance
“…MPO activity was measured in mouse tongues using a modification of the method of Chen et al (14). After mice had been killed by cervical dislocation 12 days after irradiation, tongue samples (n ¼ 10 per group) were removed and stored at À70 C until required for assay.…”
Section: Determination Of Myeloperoxidase (Mpo) Activitymentioning
confidence: 99%
“…MPO activity was measured in mouse tongues using a modification of the method of Chen et al (14). After mice had been killed by cervical dislocation 12 days after irradiation, tongue samples (n ¼ 10 per group) were removed and stored at À70 C until required for assay.…”
Section: Determination Of Myeloperoxidase (Mpo) Activitymentioning
confidence: 99%
“…MPO activity, a marker for neutrophils in inflamed tissue, was also measured in hamster cheek pouches using a modification of the method of Chen et al (26).…”
Section: Determination Of Myeloperoxidase (Mpo) Activitymentioning
confidence: 99%
“…In fact, a previous report showed decreased neutrophil infiltration as a mechanism of the antiarrhythmic effect of chronic oral administration of statins. 22 We also tried rosuvastatin in a Langendorff experiment using the same protocol with pre-ischemic pravastatin treatment and there was a similar effect to that of pravastatin ( Figure S3). These results indicate that the antiarrhythmic effects observed in the present study are not specific for pravastatin and are applicable to other statins.…”
Section: Discussionmentioning
confidence: 94%
“…22 Clinical reports showed that long-term treatment with statins is associated with a reduction in life-threatening ventricular arrhythmias in patients with coronary artery disease 23 or after reperfusion therapy for AMI. 24 In the present study, we showed that oral intake of pravastatin for 7 days conferred antiarrhythmic effects in anesthetized rats subjected to local I/R by LAD occlusion.…”
Section: Discussionmentioning
confidence: 99%